Temperature-sensitive mutants of rabies virus in mice: a mutant (ts2) revertant mixture selectively pathogenic by the peripheral route of inoculation. - Clark, H F (1976)
Analysis of the pathogenic potential in mice of a variety of rabies and rabies serogroup viruses revealed that an apparently revertant population of virus derived from CVS mutant ts 2 had a unique capacity to selectively induce paralytic disease when given by a peripheral [intraplantar (i.pl.)] route of inoculation. Little paralytic disease was induced by high concentrations of virus administered by the intracerebral (i.c.) route, whereas paralytic disease and death were characteristically induced in mice given only a few infectious doses of virus i.c. Disease induced by i.pl. inoculation was dose dependent. Mice frequently survived paralytic disease induced by i. pl. inoculation, with clinical signs often persisting indefinitely; mice surviving i.c. inoculation of high concentrations of virus frequently exhibited chronic nonspecific signs of minor debility. Analysis of the ts 2 virus population indicated that it was composed of a mixture of ts and revertant virions, each with characteristic pathogenic (or nonpatholgnic) propensities, none of which was identical to the original composite ts 2 virus populations. Despite the heterogeneity of the ts 2 virus population, the typical pathogenic pattern of selective pathogenic capicity after i. pl. inoculation at high doses was retained during 11 ocnsecutive passages in suckling mouse brain. ts 2 virus was demonstrated to interfere with the disease-producing capacity of CVS fixed rabies virus when ts 2-CVS mixtures were inoculated i.c. However, attempts to demonstrate a particular propensity for induction in vitro of "autointerference" by ts 2 in serial passage in BHK-21 cell culture inoculated at high multiplicity were unsuccessful.